Guitar Preludes by Heitor Villa-Lobos: Genre Traditions of Brazilian Music - FILATOVA, Tetiana (Studia Universitatis Babes-Bolyai Musica, 2024)
Guitar cycle of Heitor Villa-Lobos “Five Preludes” is researched in terms of the national genre traditions of various etymologies – European, African, Indian. At the level of musical language, the interaction of melodic and metro-rythmic features, connection with Portuguese Modinha, Brazilian Choro, Waltz-Choro, Afro-Brazilian Capoeira, Indian chants of the indigenous people of the country are revealed. Adaptive mechanisms of mixing genre elements on the scale of the entire cycle and each of the miniatures are designated. The features of socio-cultural environment of origin, existence of genres, as well as their participation in popular music of urban and rural life, carnival processions and tribal rituals are taken into consideration. References to Villa-Lobos’s personal experience of amateur music-making in the street Choro ensembles and ethnographic expeditions allowed correlating the timbre sound of genres in authentic folk practices with solo guitar version of their academic embodiment. Innovative technical methods of playing the guitar are indicated: shift of the stable fingering configuration along the fingerboard, introduced by the composer to modernize the language of music based on the idiomatic of the instrument. Program dedications are revealed in connection of targeted stylization of the sound atmosphere or the styles of European and Brazilian composers.